TEXTURAL AND CHEMICAL EFFECTS OF BACTERIAL ACTIVITY ON BASALTIC GLASS: AN EXPERIMENTAL APPROACH - Thorseth I.H.; Furnes H.; Tumyr O. (My University, 1995)
Naturally altered basaltic glass may show features such as pitted textures and variable degree of element mobilization relative to the fresh parent. The alteration process has generally been considered from only a chemical/physical point of view, but recent observations of bacteria in altered glass have, however, led to questions about the importance of microbial activity. In order to examine this, an experiment has been performed in which basaltic glass samples were immersed in growth media at room temperature for up to 394 days, inoculated with bacteria derived from a naturally altered pyroclastic deposit (Surtsey tuff).During the experiment it was observed that bacteria had a great affinity for attachment to the glass surface, which is in most cases connected to the production of extracellular polymers. Further, different species of bacteria were dominant at different time intervals. The bacteria activity caused a general decrease in pH from 8.0 to 5.8 during the time of the experiment.After 46 days of incubation, SEM studies of samples show rare examples of clear etching marks on the surface corresponding in size and shape of a minor group of bacteria. A local corrosion in a more irregular manner was observed after 181 days. Chemical analyses of the glass surface show no difference in composition compared to the fresh glass at this stage, i.e. any dissolution is congruent. Bacteria and biofilms attached to the glass surface show accumulation of elements, of which Al and Si could only have been derived by dissolution of the glass. However, the extent of accumulation of various elements may differ pronouncedly within and between the runs at 44, 77 and 181 days. This scatter probably reflects the diversity of the community and the ability of the different species of bacteria to accumulate elements.After 394 days the outermost glass rim, 1 μm in thickness, is highly depleted in all cations, except Si, which is relatively enriched. This incongruent dissolution of the glass, has only been active during the last 7 months of the experiment. The alteration rate is increased, at least, by a factor of 10 compared to that of the first 6 months. This is thought to be caused by the activity of a new, dominant bacterium group during this period. Microanalyses of the bacteria attached to the residual, leached glass rim, show more frequent accumulation of Si, and generally their chemistries are more homogenous than that observed in the other, shorter-termed runs.Bacterial activity may hence have a great influence on the textural and chemical developments commonly observed in naturally altered basaltic glass deposits.